Experimental research of technological properties of concrete mixing compression process under reconstruction conditions - Basarab, V.; Umanets, I. (Ways to Improve Construction Efficiency, 2022)
The article is devoted to the experimental determination of technological properties of concrete mixtures in the conditions of reconstruction of buildings and structures. The technology of construction works under erection and reconstruction largely depends on the properties of the main building materials, the peculiarities of the environment and also on the technological processes. Today, monolithic–frame construction technology is quite common, so the condition of high–quality performance of works is to determine and effectively use the properties of the concrete mixture, taking into account the methods and modes of technological processes. The relevance of doing inspections of buildings and structures in order to assess their technical condition, both in terms of operation and in terms of reconstruction or modernization was also emphasized. The purpose of work was development of a method of definition of properties of building structure during reconstruction of buildings and constructions and also algorithm of selection of a set of the experimental equipment was established. The analysis of modern methods for determining the properties of building materials and structures and analog–digital information processing devices to establish a real physical picture of changes in the stress–strain state of building structures in terms of reconstruction has been done. The method of determining the main properties of building structures using the theory of planning experiments was given. The scheme of installation of sensors and algorithm of data recording and processing of research results were given. Recommendations of using the main types of sensors and recording equipment to determine the stresses and strains that occur in building structures under operating conditions were given. Recommendations for the creation of research complexes in accordance to objectives and technological requirements were given. The main characteristics of monitoring the technical condition of building structures for the assessment and prediction of deformation processes in real time in order to minimize deviations of system parameters from operational values have been determined.